One-Year Efficacy of Expanded Polytetrafluoroethylene Vascular Graft in Eighty-Three Hemodialysis Patients - Afshar, Reza; Salimi, J; Sanavi, S R; Modaghegh, M H; Niazi, F; Fallah, N (Urology Journal, 2009)
Purpose: To evaluate the patency and efficacy of expanded Polytetrafluoroethylene (ePTFE) vascular graft in hemodialysis patients. Materials and Methods: In a prospective study from January 1999 to January 2001 at Sina hospital 41 patients underwent implantation of 6-mm vascular grafts and 42 underwent implantation of 8-mm grafts in order to make vascular assess for hemodialysis. They were followed up to 12 months, observing the complications. Results: Mean patients’ age was 52.2 years. Thirty-seven of them were females and 46 were males. Over a 12 months period of follow-up, 12 cases of graft infection (14.5%), 21 cases of thrombosis (25.3%), 7 cases with both complications (8.4%), and 1 case of pseudoaneurism (1.2%) were observed. One-year patency rate was 34.9%. Diabetes was the only factor associated with lower patency rate (27% versus 57%, p<0.05). Conclusion: ePTFE vascular graft seems to be an appropriate substitute for arteriovenous fistula as a vascular assess in hemodialysis patients. Educating patients and good care can decrease the rate of infection, thrombosis, and other complications, resulting in a better patency and lower morbidity rate.